„Und natürlich darf geschossen werden!“ - Schamm, Christoph (In:Contingentia;Porto Alegre : Universidade Federal do Rio Grande do Sul, Instituto de Letras, 2006-;Band 3, Heft 2 (2008), Seite 16-29;Online-Ressource, 2008)
In the late 1960s, West Germany was swept over by a wave of student protest. The movement of 1968 hit the country especially hard because the young generation aimed to overcome the Nazi past of their parents once and for all. As their peaceful demonstrations did not have any success, some of the leftist activists decided to take violent measures. Among other terrorist groups, the Red Army Fraction was born. This article tries to bring to light, if and how far the political poetry of the German postwar period predicted and legitimized this process.
urn:nbn:de:hebis:30:3-250519
Keywords: Online-Publikation; Politische Lyrik; Deutsch; Rote-Armee-Fraktion